Jugaad 3.0 : Hacking the Corporation to Make it Fast,Fluid and Frugal - Simone Bhan Ahuja (Portfolio / Penguin, 2019)
This book will prove that every organization's best chance, to survive and become better than ever, lies within itself. Against the decidedly progressive, action-oriented, and above all restless backdrop of disruption, the DNA of established business is starting to realign. It's the beginning of a groundswell that has started to make lean entrepreneurship a core competency within big business. Based on hundreds of interviews, as well as the author's consulting work within companies, Jugaad 3.0 Hacking the Corporation identifies the competencies these corporate hackers possess. It also offers a spectrum of carefully crafted archetypes to help people see themselves in this trend and allow organizations identify the innovators in their midst.